Assessment of toxicity and anti-plasmodial activities of chloroform fractions of Carapa procera and Alchornea cordifolia in murine models - Mahama, Ayisha; Chama, Mary Anti; Oppong Bekoe, Emelia; Asare, George Awuku; Obeng-Kyeremeh, Richard; Amoah, Daniel; Agbemelo-Tsomafo, Constance; Amoah, Linda Eva; Erskine, Isaac Joe; Kusi, Kwadwo Asamoah; Adjei, Samuel (Frontiers in Pharmacology, 2022)
Background: Plant as a source of medicine has gained international popularity in recent times because of its natural origin, availability in local communities, cheaper to purchase, ease of administration, and its usefulness as an alternative treatment in case of numerous side effects and drug resistance. However, the use of herbal formulations can also result in short-term and long-term organ damage or dysfunction to the host. In this study, chloroform fractions of the leaves of two medicinal plants, Alchornea cordifolia (ACL) and Carapa procera (CPL), were investigated for their toxicological and anti-malarial effects in murine models. Method: Acute (14-day) and sub-acute (28-day) studies were conducted based on the Organization for Economic Cooperation and Development (OECD) Guidelines in Institute for Cancer Research (ICR) mice and Sprague Dawley (SD) rats respectively. A dosage of 2000 mg/kg body weight was administered orally to each ICR mouse during the acute study and 100, 300, and 1000 mg/kg body weight to each SD rat during the sub-acute study. A 5-day curative anti-plasmodial activity was assessed in ICR mouse model. Results: The assessment of toxicity revealed that all three fractions did not influence mortality, clinical appearance, body weight gain, or necropsy at the various doses. Hematological and serum biochemical analysis indicated no significant elevations in liver and renal function parameters. Histopathological examinations of the liver indicated reversible liver degeneration with the chloroform fraction of the 100% ethanol extract of Carapa procera leaves (CPL100%) at 1000 mg/kg. Anti-plasmodial assessments showed CPL100% exhibiting dose-dependent anti-plasmodial activity from 16% to 26.67%. On the other hand, chloroform fraction of the 100% ethanol extract of Alchornea cordifolia leaves (ACL100%) showed declining anti-plasmodial activity from 21.1% to 15.1%. Conclusion: These preliminary findings demonstrate that chloroform fractions of the leaves of Carapa procera and Alchornea cordifolia may be safe agents for treating malaria hence further development for drug discovery must be pursued.